National Dissemination of Cognitive-Behavioral Therapy for Chronic Pain in Veterans. Issue 8 (August 2015) - Stewart, Michael O.; Karlin, Bradley E.; Murphy, Jennifer L.; Raffa, Susan D.; Miller, Sarah A.; McKellar, John; Kerns, Robert D.
<x xml:space="preserve">Abstract</x> Objective: This paper assesses the effects of training in and implementation of Cognitive-Behavioral Therapy for Chronic Pain (CBT-CP) in the US Department of Veterans Affairs (VA) health care system on therapists' CBT-CP competencies and patients' pain-related outcomes. Methods: A total of 71 therapists participated in the VA CBT-CP Training Program. Patients included 148 Veterans treated by therapist training participants. Therapists completed a 3-day workshop followed by 6 months of weekly consultation. Therapy session tapes were rated by expert training consultants using a standardized competency rating form. Patient outcomes were assessed with measures of patient-reported pain intensity, pain-related cognitions, overall distress, depression, pain interference, and quality of life. The therapeutic alliance was also assessed. Results: Among the 71 therapists who participated in the training program, 60 (85%) completed all training requirements, including competency-based performance criteria. Of the 148 Veteran patients treated, 117 (79%) completed all CBT-CP protocol sessions. Intent-to-treat analyses indicated significant improvements in pain catastrophizing, interference, quality of life, and other domains, as well as on the therapeutic alliance. Discussion: Training in and implementation of CBT-CP in the VA health care system were associated with significant increases in therapist competencies to deliver CBT-CP and improvements in several domains for Veteran patients. Results support the feasibility and effectiveness of broad dissemination of CBT-CP in routine, nonpain specialty settings.